(untitled) (Journal of Bio-Science, 2016)
Context: Compare the effect of different ecological conditions on phenotypical traits of Phlomis olivieri. Objective: To observe morphological variation between and within different populations of Phlomis olivieri Benth. Materials and Methods: Morphological characters of eleven populations of Phlomis olivieri were investigated in the both levels: between and within populations. Samples were collected from different parts of Iran and from each population, 3 to 4 samples were elected randomly and sixteen quantitative and qualitative morphological traits from the both vegetative and reproductive organs were examined. Results: Analysis of variance test as well as one-sample test confirmed significant variations for quantitative morphological traits. Morphological features varied between populations, consequently populations were separated from each other in the UPGMA tree and also PCO and PCA plots, among these, populations K, A, D and B placed far from others. Some degrees of polymorphism in morphological traits occurred within populations and individuals of each stand separated from others. Conclusion: This study showed that ecological factors had strong effect on morphological features of different populations of same plant species. This phenomenon was called phenotypic plasticity which created infraspecific variations at both levels interpopulation and intrapopulation or morphological polymorphism among populations. J. bio-sci. 22: 59-67, 2014